The Impact of Emotional Appeal, Workplace Environment and Social Responsibility on Students' Sense of Belonging in Higher Education Institutions - Khalikussabir; Fatkhur Rochman; Abdul Waris; Sufiyanto (Jurnal Penelitian, 2025)
Amid the wave of rapid technological advancement and intense competition in the world of education, higher education institutions are not only required to provide quality academic services but also to build strong emotional bonds with students. Sense of belonging becomes the main indicator that influences learning motivation, academic satisfaction, and student loyalty to their alma mater. This study uses an explanatory research design with a sample of 120 students taken through the accidental sampling technique. Data were collected using a questionnaire that had undergone validity and reliability tests and then analysed using descriptive statistics and multiple linear regression. The research results show that emotional appeal, workplace environment, and social responsibility have a significantly positive impact on students' sense of belonging. The workplace environment has the most dominant influence, emphasising the importance of a comfortable and supportive campus environment, while emotional appeal strengthens the affective bond, and the factor of social responsibility can enhance students' pride and sense of ownership towards the higher education institution. These three factors together build a meaningful and sustainable sense of belonging for students. Therefore, higher education institutions are expected to strategically integrate all three to enhance student engagement while also strengthening academic experience, retention, and institutional competitiveness, and fostering long-term commitment to their alma mater.